2019
DOI: 10.1016/j.ica.2019.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Defining the origins of multiple emission/excitation in rhenium-bisthiazole complexes

Abstract: The underlying mechanism of the unusual emissive behavior of [Re(CO)3-1,1bisthiazole-(1,4)-diaminobutane)] bromide (4-BT) has been investigated. Synthesis and spectroscopic characterization of structurally similar isomers ([Re(CO)3-1,1-bis-2-thiazole-(1,4)diaminobutane)] bromide (2-BT) and , location of triplet states, solid state and low temperature spectroscopic measurements, and DFT calculations show that the photophysical properties are not due to photoisomerization as previously hypothesized. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License isolated from the fruits and flowers of the Cannon ball tree (Couroupita gueanensis), thereafter its good antioxidant, antibacterial and anticancer properties have also been established (Premanathan et al, 2012;Guo, 2019;Ding et al, 2020). Coogan et al (2009) and Azzarelli et al (2019) have also shown that heavy metals are not just "poisonous", but also possess great biological importance through the synthesis of several novel d 6 transition organometallic based agents, which were also used to target specific biological entities. Therefore, the coordination of Re(I) to isatin Schiff bases is promising with prospective biological activities which could even target biological entities of cancerous cells and could also possess some therapeutic anticancer effects.…”
Section: Introductionmentioning
confidence: 98%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License isolated from the fruits and flowers of the Cannon ball tree (Couroupita gueanensis), thereafter its good antioxidant, antibacterial and anticancer properties have also been established (Premanathan et al, 2012;Guo, 2019;Ding et al, 2020). Coogan et al (2009) and Azzarelli et al (2019) have also shown that heavy metals are not just "poisonous", but also possess great biological importance through the synthesis of several novel d 6 transition organometallic based agents, which were also used to target specific biological entities. Therefore, the coordination of Re(I) to isatin Schiff bases is promising with prospective biological activities which could even target biological entities of cancerous cells and could also possess some therapeutic anticancer effects.…”
Section: Introductionmentioning
confidence: 98%